Outbreaks of streptococcosis associated with Streptococcus agalactiae in farmed climbing perch (Anabas testudineus) in Vietnam - Tu Thanh Dung; Quach Van Cao Thi; Nguyen Bao Trung (Veterinary Integrative Sciences)
Streptococcus agalactiae causes serious economic damage to fish cultivation worldwide. The goal of this work was to isolate, identify, and evaluate the pathogenicity and susceptibility of the streptococci isolates to antibiotics recovered from climbing perch (A. testudineus) farmed in the southern part of Vietnam. Moribund and healthy fish were taken differently from intensive climbing perch farms. The diseased fish’s clinical signs were observed, including darkened body color, ascites, hepatomegaly, an enlarged kidney, and splenomegaly. Based on the conventional method, the API 20 Strep test, and 16S rRNA gene partial sequencing, S. agalactiae was associated with disease. They have non β-hemolytic activity, gram-positive cocci, catalase, and oxidase-negative enzymes. The LD50 trial performance of S. agalactiae showed the virulence of this bacteria in climbing perch and fulfilled Koch’s postulates with a value of 8.71 x 104 CFU/mL at day 7. Most of the challenged fish presented the same clinical signs as the natural infection. Hence, S. agalactiae were confirmed as the causative agents of the "dark body" disease. Antibiogram results demonstrated that S. agalactiae strains were completely susceptible to cefotaxime, doxycycline, and florfenicol. Interestingly, the results of this study found that S. agalactiae isolates are 100% resistant to sulfamethoxazole-trimethoprim. To the best of our knowledge, this is the first report of S. agalactiae as a pathogen of climbing perch.